ISEcp1-Mediated Transposition and Homologous Recombination Can Explain the Context of bla(CTX-M-62) Linked to qnrB2 - Zong, Zhiyong (American Society for Microbiology (ASM), 2010)
bla(CTX-M-62), a C508T variant of bla(CTX-M-3b), was transferred from Klebsiella pneumoniae JIE137 on a conjugative plasmid together with a class 1 integron containing the dfrA12-gcuF-aadA2 cassette array, ISCR1, and qnrB2. bla(CTX-M-62) lies between intact and rearranged copies of ISEcp1 in a configuration that can be explained by a combination of transposition and homologous recombination and which also illustrates the ability of ISEcp1 to mobilize an adjacent gene as part of transposition units of different sizes.